2021
DOI: 10.1038/s41598-021-88672-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of a Type B chloramphenicol acetyltransferase from the emerging pathogen Elizabethkingia anophelis NUHP1

Abstract: Elizabethkingia anophelis is an emerging multidrug resistant pathogen that has caused several global outbreaks. E. anophelis belongs to the large family of Flavobacteriaceae, which contains many bacteria that are plant, bird, fish, and human pathogens. Several antibiotic resistance genes are found within the E. anophelis genome, including a chloramphenicol acetyltransferase (CAT). CATs play important roles in antibiotic resistance and can be transferred in genetic mobile elements. They catalyse the acetylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…; Table S2: Potential virulence-associated features among Elizabethkingia spp. as predicted using the Virulence Factor Database (VFDB) [ 39 , 40 , 41 , 43 , 44 , 46 , 59 , 60 , 61 , 62 , 72 , 73 , 77 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 ].…”
mentioning
confidence: 99%
“…; Table S2: Potential virulence-associated features among Elizabethkingia spp. as predicted using the Virulence Factor Database (VFDB) [ 39 , 40 , 41 , 43 , 44 , 46 , 59 , 60 , 61 , 62 , 72 , 73 , 77 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 ].…”
mentioning
confidence: 99%
“…Previous studies have shown that in Cats, residues Y30, S32, and H79 are located at the active site and can form hydrophilic contacts with chl. 21,25 In CatB8, R51 has the potential to establish a hydrogen bond with chl: 3, while residues N20 and D41 may participate in interactions with chl: 4, Q77 may interact with chl: 1 and 2, and E94 can interact with chl: 3 (Figure 4).…”
Section: ■ Resultsmentioning
confidence: 99%
“…Chl has antibiofilm properties and can effectively kill various bacteria and prevent colony growth. 25,33 However, owing to the severe side effects of chl, it has not been the first choice for treating internal bacterial infection. Instead, it is more widely used for topical treatment or some ocular infections.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All isolates carry the L1 metallo-β-lactamase, as well as sul4 ( 24 ). ACYCe.8N also carries sul2 , katG ( 25 ), and catB11 ( 26 28 ).…”
Section: Announcementmentioning
confidence: 99%